Answer:
he has received negative positive punishment...? I"M SORRY IF IT"S WRONG!!!
Step-by-step explanation:
Answer:
The solution is ![x = \frac{1}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
To solve this exponential equation, we must write both sides as powers of 3.
The equation given is:
![3^{7x + 4} = (\frac{1}{27})^{x-3}](https://tex.z-dn.net/?f=3%5E%7B7x%20%2B%204%7D%20%3D%20%28%5Cfrac%7B1%7D%7B27%7D%29%5E%7Bx-3%7D)
Since
, we have that
, so![\frac{1}{27} = 3^{-3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B27%7D%20%3D%203%5E%7B-3%7D)
Then
![3^{7x + 4} = (\frac{1}{27})^{x-3}](https://tex.z-dn.net/?f=3%5E%7B7x%20%2B%204%7D%20%3D%20%28%5Cfrac%7B1%7D%7B27%7D%29%5E%7Bx-3%7D)
![3^{7x + 4} = (3^{-3})^{x-3}](https://tex.z-dn.net/?f=3%5E%7B7x%20%2B%204%7D%20%3D%20%283%5E%7B-3%7D%29%5E%7Bx-3%7D)
![3^{7x + 4} = 3^{-3(x-3)}](https://tex.z-dn.net/?f=3%5E%7B7x%20%2B%204%7D%20%3D%203%5E%7B-3%28x-3%29%7D)
![3^{7x + 4} = 3^{-3x + 9}](https://tex.z-dn.net/?f=3%5E%7B7x%20%2B%204%7D%20%3D%203%5E%7B-3x%20%2B%209%7D)
Since both sides are now powers of 3, we can equal them:
![7x + 4 = -3x + 9](https://tex.z-dn.net/?f=7x%20%2B%204%20%3D%20-3x%20%2B%209)
![10x = 5](https://tex.z-dn.net/?f=10x%20%3D%205)
![x = \frac{5}{10}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B5%7D%7B10%7D)
![x = \frac{1}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
The solution is ![x = \frac{1}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
this is using the straight line depreciation formula. you take the initial amount and subtract the amount that it loses each year times x
Answer:
s(2x8)
Step-by-step explanation: